Clinical outcomes of IgA nephropathy patients with different proportions of crescents. Issue 11 (March 2017) - Zhang, Wang; Zhou, Qian; Hong, Lingyao; Chen, Wenfang; Yang, Shicong; Yang, Qiongqiong; Chen, Wei; Yu, Xueqing
Abstract : Abstract: Crescents involving more than 50% of glomeruli in IgA nephropathy (IgAN) signify a rapid deterioration of renal function. However, little is known about the prognosis of IgAN patients presenting crescents in less than 50% of glomeruli. We aimed to investigate the clinicopathological characteristics and outcomes of IgAN patients with different proportions of crescents. From January 2000 to December 2011, biopsy-proven primary IgAN patients with histological crescents formation were enrolled in this retrospective cohort study. The patients were divided into 4 groups on the basis of crescent proportion as follows: <5%, 5% to 9%, 10% to 24%, and ≥25%. The primary endpoint was defined as the doubling of baseline serum creatinine (SCr) and/or end-stage renal disease (ESRD), and the secondary endpoint was death. A total of 538 crescent-featured IgAN patients were followed up and included in the analysis. The median crescent proportion was 8.0%. An increasing crescent proportion was associated with a reduced estimated glomerular filtration rate (eGFR), decreased level of hemoglobin, and increased amount of urine protein excretion. After a median follow-up period of 51 months (range 12–154 months), the endpoint events-free survival rate of the above 4 groups were 69.9%, 47.7%, 43.8%, and 40.6%, respectively (Log rank=13.7, P = 0.003), when we incorporated death with renal outcome as a composite endpoint. Multivariate Cox regression analyses adjusting for eGFR, hypertension, proteinuria, and the Oxford-MEST classification demonstrated the predictive significance of an increasing crescent proportion with renal survival and mortality (each increase by 5% [log-transformed]: HR=1.51, 95% CI 1.08–2.11, P  = 0.02). Further comparisons of patients with small proportions of crescents (<5%) and those absent of such pathological lesion showed that the 2 groups of patients had comparable prognosis. An increasing crescent proportion was identified as an independent predictor for unfavorable clinical outcomes in IgAN. Therefore, a small proportion of crescents, over 5% particularly, should be paid more attention in clinical practice. Abstract : Supplemental Digital Content is available in the text